2002
DOI: 10.1016/s0304-4165(02)00270-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced delivery of naked DNA to the skin by non-invasive in vivo electroporation

Abstract: DNA delivery to skin may be useful for the treatment of skin diseases, DNA vaccinations, and other gene therapy applications requiring local or systemic distribution of a transgene product. However, the effective, consistent and patient-friendly transfection of skin cells remains a challenge. In a mouse model, we evaluated the effectiveness of intradermal injection of plasmid DNA followed by noninvasive in vivo electroporation (EP) as a method to improve transfection in skin. We achieved a several hundred-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 48 publications
2
95
0
Order By: Relevance
“…25 This physical technique has been previously used by different groups including ours to locally deliver siRNAs in various tissues. [29][30][31][32][33][34][35][36] As reported previously we observed that the electrical treatment itself had no detectable effect on tumor growth. Takahashi and coworkers 23 recently found that EP following injection in mouse melanoma tumors slightly improved the uptake of a plasmid encoding luciferase and subsequently attempted this approach for treatment of the tumors with siRNAs or plasmids encoding shRNAs.…”
Section: Rna Extraction and Quantitative Real-time Pcrsupporting
confidence: 85%
See 1 more Smart Citation
“…25 This physical technique has been previously used by different groups including ours to locally deliver siRNAs in various tissues. [29][30][31][32][33][34][35][36] As reported previously we observed that the electrical treatment itself had no detectable effect on tumor growth. Takahashi and coworkers 23 recently found that EP following injection in mouse melanoma tumors slightly improved the uptake of a plasmid encoding luciferase and subsequently attempted this approach for treatment of the tumors with siRNAs or plasmids encoding shRNAs.…”
Section: Rna Extraction and Quantitative Real-time Pcrsupporting
confidence: 85%
“…In rodents, EP have been used to deliver siRNAs in various organs such as skin, 29 eyes, 30 brain, 31 muscles, 32,33 joint tissue 34,35 and kidney. 36 However, delivery of large nucleic acids (plasmids) have been found to be poorly efficient in solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…For electroporation gene delivery to skin, plasmid DNA may be injected intradermally [1][2][3][4][5][6][7][8][9][10] or biolistically. 11 Pulses are applied to the skin surface or through penetrating (needle) electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Caliper, plate, tweezer or clip type electrodes grip a fold of skin. 1,[4][5][6]9,10 The meander 7,11 and the N1/ N2 electrode 8 are simply pressed against the injected region. The applied pressure may vary.…”
Section: Introductionmentioning
confidence: 99%
“…3 Electroporation has since been shown to enhance gene transfer in other tissues including synovium, 4 spinal cord, 5 and skin. 6 Effective delivery of naked DNA to skeletal muscle is also facilitated by the increase in hydrostatic pressure caused by rapid injection of a large volume of DNA intravenously (i.v.) into a limb with occluded blood supply.…”
Section: Naked Dnamentioning
confidence: 99%